HUBUNGAN EFIKASI DIRI DIGITAL DENGAN LITERASI DIGITAL PADA SISWA SEKOLAH MENENGAH KEJURUAN (SMK) BIDANG KEAHLIAN MULTIMEDIA DI KOTA SALATIGA - Wisnu Ardani,; Enjang Wahyuningrum, (Journal of Innovation Research and Knowledge, 2025)
This study aims to examine the relationship between digital self-efficacy and digital literacy among vocational high school (SMK) students majoring in multimedia in Salatiga City. This research employed a correlational quantitative approach involving 148 students from four vocational schools in Salatiga. Data were collected using the Digital Self-Efficacy Scale by Anna-Sophie Ulfert-Blank and Isabelle Schmidt (2022) and the Digital Literacy Scale by Anwar et al. (2023). The data were analyzed using the Pearson Product-Moment correlation test. The result showed a significant positive relationship between digital self-efficacy and digital literacy. These findings indicate that students with higher levels of digital self-efficacy tend to have higher levels of digital literacy. The implication of this study highlights the importance of strengthening digital self-efficacy to improve digital literacy, especially in technology-based educational environments